Evaluation of Cortisol Production in Aldosterone-Producing Adenoma - Inoue, Kosuke; Yamazaki, Yuto; Tsurutani, Yuya; Suematsu, Sachiko; Sugisawa, Chiho; Saito, Jun; Omura, Masao; Sasano, Hironobu; Nishikawa, Tetsuo (Hormone and Metabolic Research, 2017)
Aldosterone-producing adenoma (APA) is sometimes accompanied with subclinical hypercortisolism. We investigated the ability of cortisol production in APA, both clinically and pathologically. A retrospective cohort study was conducted at Yokohama Rosai Hospital from 2009 to 2016. Thirty patients with APA and serum cortisol levels during the 1 mg dexamethasone suppression test (F-DST)<3.0 μg/dl were included. We evaluated the 1) difference between pre-adrenalectomy F-DST (pre-F-DST) and post-adrenalectomy F-DST (ΔF-DST), 2) correlation between ∆F-DST and pre-F-DST, tumour size determined by CT, and type of adrenalectomy (total or partial), and 3) relationship between the ratio of F-DST divided by tumour size (ΔF-DST/pre-F-DST/mm) and immunoreactivity of CYP17A1, CYP11B1, and CYP11B2. The median [interquartile range] age was 48 [38–58] years. We found a significant decrease in F-DST after adrenalectomy [before: 1.4 (1.1–1.8); after: 0.9 (0.6–1.2); p<0.001]. Additionally, a significant correlation was found for ΔF-DST and both pre-F-DST (Spearman, ρ=–0.68, p<0.001) and tumour size (ρ=–0.51, p 0.005). No significant difference was found in ΔF-DST between total and partial adrenalectomy. CYP17A1 and CYP11B1 were positive in 21 (100%) and 17 (81%) adenomas, respectively. CYP17A1 immunoreactivity in the tumour was significantly related with ΔF-DST/pre-F-DST/mm (p 0.049). F-DST significantly decreased after adrenalectomy, and most of the adenomas were immunohistochemically positive for CYP17A1 and CYP11B1 as well as CYP11B2. We should consider the possibility of autonomous cortisol production as well as hyperaldosteronism in the evaluation and treatment of APA patients.
Keywords: aldosterone producing adenoma; cortisol; dexamethasone suppression test; CYP17A1